ANALISIS KINERJA DOSEN AKUNTANSI DALAM MENGAJAR TERHADAP MAHASISWA POLITEKNIK NEGERI TANAH LAUT MENGGUNAKAN METODE TREND - Gautama, Muhammad Shapiq; Kamil, Insan; Rahmawati, Neng Ayu (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2020)
Lecturer performance must be assessed so that we know the quality of the lecturer. Thus, students can gain more knowledge from the lecturer and be organized. This study uses the Trend analysis method where there are 13 lecturers in Accounting Study Program, the State Polytechnic of Tanah Laut. The trend analysis method is a method that can figure out the increase and decrease of objects to be studied or can predict the condition of the data in the future. The results of the analysis showed that there were several lecturers who experienced an increase or decrease in the teaching process, in terms of the increase because the lecturer was able to dilute the atmosphere and was easy in delivering the material and in terms of the decline, the lecturer was less able to dilute the atmosphere so that sometimes the student could get sleepy. Therefore, lecturers must be able to break the ice so that students can accept what is explained.